Sectoral Stock Performance During Ramadan: Comparative Evidence from Indonesia - Perdana, Yuda Mahesa; Rusgianto, Sulistya (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This study aims to compare three stock sectors in Indonesia, namely the consumer goods, financial, and transportation sectors during the Ramadan period of 2020-2024, using the Kruskal-Wallis test. The data was taken from the daily closing prices of stocks in the consumer goods, financial, and transportation sectors listed on the ISSI index. The results of this study indicate that there is no significant abnormal return difference among the three stock sectors, with a significance value of 0.482. However, the financial sector showed a positive mean return compared to the other sectors. The limitations of this study lie in the scope of the three sectors and the time period of the research, while the implications suggest that the financial sector can be considered by investors for their portfolios, as it tends to be more stable than the other sectors during Ramadan.